Obtaining SiC fibers–PyC interfacial properties through push-out FEM Models - Martinez-Pechero, A; Zayachuk, Y; Widdowson, A; Armstrong, DEJ; Tarleton, E (Elsevier, 2023)
Silicon carbide (SiC) has attractive properties for use in nuclear reactors. However, it is hampered by inherent brittleness that is overcome through a fiber-reinforced composite. A finite element model based on cohesive zone contact coupled to Coulomb friction is proposed to simulate the push-out response of isolated fibers in SiC/PyC fiber-reinforced composites. The model reproduces the measurements obtained during push-out experiments of isolated fibers in different configurations and predicts interfacial failure between the PyC interphase and fiber. The brittle properties predicted coincide with literature indicating that fiber–PyC interface could prevent the crack propagation through the fiber, fulfilling the function of the structure.